THE IMPLEMENTATION OF PROJECT BASED LEARNING (PjBL) IN TEACHING AND LEARNING ENGLISH AS A FOREIGN LANGUAGE - Setiawan, Wawan (2016)
This study entitled "the Implementation of Project Based Learning (PjBL) in Teaching and Learning English as a Foreign Language" was conducted: (1) to describe the teacher's process of teaching and learning English by implementing project based learning, and (2) to identify the teacher's difficulties in implementing project based learning in teaching and learning English. The data in the form of document analysis, observations, and interviews were taken from an English teacher at a Junior High School in Bangka Tengah. To analyze the data, theory of a descriptive qualitative was implemented. The findings showed that: First, the teacher implemented project-based learning by conducting several steps starting from the planning until the evaluation. Those steps can be categorized as follows: (1) planning the projects (2) modifying the teaching scenarios and teaching assessment (3) applying the teaching scenarios (4) assessing the projects. Second, the teacher stated that she faced some difficulties in implementing PjBL. The difficulties were related to some factors such as classroom management, students learning support, limited time, and assessment. In addition, teacher's solutions to overcome those difficulties as follows: first, to overcome the difficulty in relation to classroom management is by monitoring students' learning activities in the school area, grouping the students based on their heterogeneous ability, and controlling the running of group discussion. Second, to overcome lack of students learning support, the teacher used the power point and video to motivate them. Third, to overcome the limited time, the teacher added extra times. Fourth, to overcome the difficulty in assessment, teacher applied peer assessment.;-- Penelitian ini berjudul "the Implementation of Project Based Learning (PjBL) in Teaching and Learning English as a Foreign Language" bertujuan untuk (1) mendeskripsikan proses guru dalam kegiatan belajar dan mengajar Bahasa Inggris dengan menggunakan model pembelajaran Project Based Learning, dan (2) untuk menemukan kesulitan-kesulitan guru dalam mengimplementasikan Project-Based Learning dalam pembelajaran Bahasa Inggris. Data berupa dokumen analysis, observasi, dan wawancara bersumber dari seorang guru Bahasa Inggris di salah satu SMP di Bangka Tengah. Untuk menganalisis seluruh data yang dihimpun, penelitian ini menggunakan metode descriptive qualitative. Hasil dari penelitian ini menunjukkan: pertama, guru mengimplementasikan PjBL dengan melakukan langkah-langkah mulai dari persiapan sampai dengan evaluasi. Langkah-langkah tersebut dikategorikan sebagai berikut: (1) merencanakan proyek (2) merancang skenario dan penilaian pembelajaran (3) mengaplikasikan skenario pembelajaran (4) mengevaluasi proyek. Kedua, guru mengalami kesulitan dalam mengimplementasikan PjBL. Kesulitan-kesulitan tersebut disebabkan oleh beberapa faktor seperti manajemen kelas, kemampuan siswa, keterbatasan waktu, dan penilaian. Oleh karena itu, solusi guru dalam mengatasi kesulitan-kesulitan tersebut antara lain: pertama, untuk mengatasi kesulitan dalam manajemen kelas, guru mengawasi kegiatan pembelajaran siswa dilingkungan sekolah, mengelompokkan siswa berdasarkan kemampuan mereka yang berbeda-beda, dan mengontrol kegiatan diskusi. Kedua, untuk mengatasi kelemahan siswa, guru menggunakan media power point dan video untuk memoivasi mereka. Ketiga, untuk untuk mengatasi keterbatasan waktu, guru mengalokasikan waktu tambahan. Keempat, untuk mengatasi kesulitan dalam melakukan penilaian, guru mengaplikasikan penilaia sejawat